Incongruence in the Definition of Land Rights in National Agrarian Law: A Path to Legal Uncertainty - Mahfud, Muh. Afif; Chin Chin, Sia (LAW REFORM, 2024)
Legal certainty as one of the goals of national land law will not be created when there is incongruence in the definition of land rights in regulations. This incongruity may affect the formation, implementation and interpretation of law in the agrarian sector. The aim of this article is to analyze the incongruence in the definition of land rights in regulations and the impact of this incongruence in the definition. Based on the analysis, it is concluded that there is an inconsistency in the definition of land rights in Government Regulation no. 18 of 2021 which states that the authority for land rights covering above the ground and underground space is not in line with PP (Government Regulation) No. 43 of 2021. The regulation states that the authority for land rights does not cover the space above the ground and underground space. This misalignment includes horizontal incongruity, formal incongruity and substantive incongruity. It will result in unclear meaning of land rights, loss of predictability of regulations, and affecting the formation, enforcement and interpretation of laws so that there is no clear reference for the community and law enforcers in acting. Ultimately, this will affect legal protection for the community in exercising their rights. It is recommended that the government harmonize the definition of regulatory land rights.